The function of multi-national characters, alien settings and diverse mores in EM Forster's three international novels: "Where Angels Fear to Tread", 1905, "A Room with a View", 1908, and "A Passage to India", 1924 - Sehgal, Rajinder Paul (University of Ottawa (Canada), 1973)
Abstract not available.
Keywords: Literature, English.